2008
DOI: 10.1002/lsm.20594
|View full text |Cite
|
Sign up to set email alerts
|

The effects of radiofrequency on skin: Experimental study

Abstract: Background and Objective: Radiofrequency represents the most recent skin-rejuvenation treatment. The aim of this study was to study the changes in tissues and cells, as well as in the thickness and structure of the skin of guinea pigs following several sessions of radiofrequency. Materials and Methods: Six sessions (1 session/week) of radiofrequency (Thermafine Lift device, Grupo Solilá ser, S.L., Girona, Spain) were applied to the skin of guinea pigs. Biopsies were taken following each session and 2 months fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 25 publications
(37 reference statements)
0
21
0
4
Order By: Relevance
“…The mechanism of action after radiofrequency treatment is thought to be that of immediate collagen fibril contraction, followed by secondary collagen production and remodeling (16). Recently, Alvarez et al noted an expansion of the papillary dermis due to edema and vascular congestion followed by an increase in the thickness, cellularity (fibroblasts and histiocytes) and an accumulation of mucopolysaccharide, collagen and elastic fibers after radiofrequency treatment (17).…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism of action after radiofrequency treatment is thought to be that of immediate collagen fibril contraction, followed by secondary collagen production and remodeling (16). Recently, Alvarez et al noted an expansion of the papillary dermis due to edema and vascular congestion followed by an increase in the thickness, cellularity (fibroblasts and histiocytes) and an accumulation of mucopolysaccharide, collagen and elastic fibers after radiofrequency treatment (17).…”
Section: Discussionmentioning
confidence: 98%
“…These changes were followed by an increase in cellularity and an accumulation of intercellular substances. Subsequently, increases in collagen, elastic fibers, and mucopolysaccharides were observed 21 . These changes led to increased dermal thickness and collagen content 21 .…”
Section: Discussionmentioning
confidence: 99%
“… 21 used animal models to reveal interesting results on the effects of RF treatment on dermal cellularity and collagen formation. They found changes in the papillary dermis in the form of an expansion related to edema and vascular congestion 21 . These changes were followed by an increase in cellularity and an accumulation of intercellular substances.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Alvarez et al [40] using animal models, they showed interesting results of RF treatment on dermal cellularity and collagen formation in guinea pigs. The most relevant changes were seen in the papillary dermis, which underwent expansion as a result of edema and vascular stimulation.…”
Section: Use Of Rf Devices For the Treatment Of Cellulitementioning
confidence: 99%